Drying behavior of the marketed mushrooms Lactarius deliciosus and Agaricus bisporus - Silva, Ana Cândida (2013)
Wild edible mycorrhizal mushrooms have great commercial importance, as well as beneficial properties, linked to their nutritional value, delicacy and flavor. Lactarius deliciosus is appreciated worldwide, being frequently used in the preparation of several culinary dishes. On the other hand, Agaricus bisporus is a commercial mushroom also quite used. However, mushrooms are extremely perishable and shelf life of fresh mushrooms is very short. Therefore, they are frequently processed, being dehydration one of the possible preservation methods. The aim of the present work was to compare the forced convective hot-air drying of L. deliciosus and A. bisporus in respect to their drying kinetics. Slices of both species were obtained, immediately weighed and placed into Petri dishes. Afterwards, these slices were hot-air dried at 45ºC, being samples removed and weighted at regular interval of times. Moisture contents, drying rates and moisture ratios were determined. L. deliciosus and A. bisporus had 92.64±0.58% and 89.21±1.90% initial moisture contents (wet basis). It could be seen for both species that moisture removal was very fast at the beginning of the drying process, having the drying rate slowed down as the drying had proceeded. Some differences were detected between both species. 36 minutes were necessary to achieve a final moisture content of 1 g water/g dry matter with the A. bisporus, on contrary to the 70 minutes needed for the L. deliciosus. In order to simulate the drying behavior of these species, the suitability of some mathematical models was determined by statistical analysis. Adjusted r-squares higher than 0.95 were obtained.